Assessment of Escherichia coli Contamination in Drinking Water from Refill Depots - Savitri, Lisa; Kholis, Muhammad Akbar Nur; Prasetyawan, Fendy; Saristiana, Yuneka; Amanda, Cornelia; Mebung, Konradus Klala (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Refill Drinking Water Depots (DAMIU) have become a popular source of drinking water in Indonesia due to their affordability and accessibility. However, concerns about hygiene and microbial contamination persist, particularly in areas with limited health oversight. This study aimed to evaluate the microbiological quality of refilled drinking water in Kediri City by detecting the presence of Escherichia coli as an indicator of fecal contamination. A descriptive, cross-sectional design involving 22 depots selected based on hygiene criteria was employed. Microbiological analysis used the Most Probable Number (MPN) method, with confirmatory tests including IMViC and Eosin Methylene Blue (EMB) media. The results showed that 20 of 22 depots met the microbiological safety standard of 0 CFU/100 mL for E. coli as set by the Indonesian Ministry of Health and national standards (SNI 3554:2015). Two samples (5 and 7) tested positive for E. coli, likely due to environmental contamination, inadequate sanitation, and poor water handling practices. The positive samples demonstrated typical E. coli characteristics in IMViC (++-+) and gas formation in BGLB media. This study underscores the importance of routine surveillance, public health regulation enforcement, and improved hygiene practices in refilled water depots. Ensuring the microbiological safety of refilled drinking water is essential to prevent waterborne diseases such as diarrhea. The findings call for enhanced collaboration between local health offices and depot operators to maintain clean and safe drinking water standards across communities.